PERAN MEDIA SOSIAL DALAM MENINGKATKAN PENJUALAN TERHADAP IMPLEMENTASI STRATEGI PEMASARAN DI KEDAI SEDOTMEN BEKASI - Fauzi, Achmad; Lestari, Puji; Wardhani, Dian Kusuma; Permatasari, Selvia Annisa; Bagasasi, Faizal; Putri, Cinka Amalia; Ottay, Merry Louis; Setyakinasti, Sabrina (LPPM Institut Pendidikan Nusantara Global, 2023)
Currently, many individuals use social media as a tool for various activities in the Digital Era. One of its common uses is as a means of marketing or promoting products and services. Nowadays, businesses have an easier time marketing their goods on social media sites like Facebook, Instagram, Twitter, and others. This article's qualitative research approach, which uses words to describe research findings, allows for a deeper analysis. This article's goal is to expose the marketing tactics used by Sedotmen Bekasi's sales team. The results of the study demonstrate that using social media to implement marketing strategies has a noticeable positive impact on increasing sales.